Penerapan Media Pembelajaran Interaktif pada Mata Pelajaran Pendidikan Islam di Yayasan Al-Uyun Lebak - Hasan Maulana; Nafan Tarihoran; Hunainah Hunainah; Wasehudin Wasehudin (ISLAMIKA, 2023)
This research aims to describe the strategy and application of interactive learning media in Islamic education subjects at the Al-Uyun Lebak foundation. This research uses qualitative research that produces descriptive data. The research location is at the Al-Uyun Lebak Foundation, when the research was carried out on 2-19 December 2022. The research subjects were the Head of the Foundation, and Education Staff & Educators (Islamic education teachers), as well as students. While the research object is focused on PAI interactive learning media at the Al-Uyun Lebak Foundation. The research population is all students at the Al-Uyun Lebak Foundation, for a research sample of 10 (ten) people. Data collection techniques are through interviews, documentation, and observation. Data analysis through data reduction, then data display, inference and verification. The results of the research are related to the strategy used in interactive learning media, which refers to the steps for making material with the SlideDog application in the application of PAI learning subjects. Regarding the application of interactive learning media in PAI subjects, the material for prayer procedures using the SlideDog application is designed as attractive as possible with the addition of prayer practice videos, in practice it runs smoothly even though there are several obstacles, but they can still be handle.